Kualitas Pelayanan Perizinan pada Badan Penanaman Modal dan Pelayanan Perizinan Terpadu (BPMP2T) Kota Padang - Kristanti, Dwi; Murti, Purwaningdyah (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
This studyexamines thequality ofpublic servicesin theBoard of InvestmentandLicensingServices(BPMP2T) Padang Town. The theoryis usedasa knifeanalysis in this studyisthe conceptofpublicservice, excellent serviceandquality of service. The approachusedinthisresearchisquantitativedescriptiveapproach. The research datawasobtainedthroughquestionnairesandobservationtechniques. The respondentsof this studyof 100people. Descriptively, the qualityof serviceinBPMP2TPadang Town is good. Somevariableshave astronginfluenceinthe quality of services, such asphysicalVisibilityvariable, reliability, responsiveness.Meanwhile, the variableability, decency, security, access, the quality of service,communicationandunderstandingisveryweak.